The Influence of Product Quality, Electronic Word of Mouth and Brand Image on Repurchase Intention in Coffee-To-Go Stores with Consumer Satisfaction as Intervening Variables - Muhammad Mufashih; Ahmad Maulana; Muchsin Saggaf Shihab (Ridwan Institute, 2023)
This research aims to examine the effect of product quality, electronic word of mouth (e-WOM), and brand image on consumer satisfaction, as well as the influence of product quality, e-WOM, and brand image on repurchase intention in coffee-to-go stores, with consumer satisfaction as an intervening variable. This research was conducted to gain a better understanding of the factors that affect consumer satisfaction and the intention to repurchase the product. This research method uses a quantitative approach involving 300 respondents who are coffee-to-go shop consumers. Data is collected through the use of questionnaires that include questions about product quality, e-WOM, brand image, consumer satisfaction, and repurchase intention. Data analysis is done using multiple regression techniques and path analysis. The results show that product quality has a significant influence on consumer satisfaction, which supports the H1 hypothesis. In addition, e-WOM and brand image also have a significant influence on consumer satisfaction, which supports the H2 and H3 hypotheses. Furthermore, product quality and e-WOM also have a significant influence on repurchase intention, which supports the H4 and H5 hypotheses. Brand image also has a significant influence on repurchase intention, according to the H6 hypothesis. In addition, the findings of this study show that consumer satisfaction mediates the relationship between product quality, e-WOM, and brand image with repurchase intention, which supports the H7 hypothesis. This research provides practical implications for coffee-to-go stores to increase consumer satisfaction and the intention to repurchase products. Improving product quality, managing e-WOM positively, and strengthening a positive brand image can increase customer satisfaction and encourage repurchase intention.